Phytochemical assessment of Iphiona aucheri (Bioss.) Anderb. and its cytotoxic, antioxidant and antidiabetic activities - Shah, Muhammad Abdur Rehman; Khan, Rahmat Ali; Ahmed, Mushtaq (Bangladesh Journal of Botany, 2020)
The presence of phytochemical constituents and estimation of total phenolic contents in Iphiona aucheri (Bioss.) Anderb. stem and assessment of their cytotoxic, total antioxidant and anti-diabetic activity were investigated. All fractions were assessed for phytochemicals, cytotoxic activity, total phenolic contents, antioxidant and anti-diabetic characteristics. Saponins, glycosides, protein and amino acids, carbohydrates and flavonoids were found in aqueous fraction and methanolic extract while they were absent in n-hexane fraction except glycosides and protein. The crude methanolic extract (70.3 ± 1.9%) revealed highest brine shrimp mortalities. Except n-hexane fraction others indicated considerable antioxidant activities via DPPH, ABTS•+ and H2O2 assays. Crude methanolic extract expressed higher inhibition of α-amylase (60.71 ± 0.89%) than glucophage (54.92 ± 0.56%). Non significant correlation of total phenolic contents with percentage antioxidant and anti-diabetic activities of crude methanolic extract and its various fractions was observed in all cases.